ANALISIS PELAKSANAAN EKSTRAKURIKULER PRA PEMBELAJARAN FORMAL SISWA DI SMP SWASTA AN-NIZAM - Suhara, Shakila Putri; Siahaan, Amiruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the strategic measures undertaken by madrasah principals in responding to resistance to change during the implementation of the Kurikulum Merdeka (Independent Curriculum), with the research conducted at Madrasah Aliyah Mutiara Aulia Sei Mencirim Sunggal. The study employed a qualitative approach with a descriptive method, in which data were collected through three primary techniques: direct observation, interviews, and document review. The findings reveal that teachers' resistance to curriculum change manifested in several forms, including a weak conceptual understanding of the Kurikulum Merdeka, difficulties in implementing project-based learning models, limited competence in operating educational technology, and a tendency to retain conventional mindsets that were less open to innovation. In addressing these challenges, the principal adopted a strategic approach by optimizing management functions. The planning stage was carried out through socialization with teachers and the collaborative development of work programs. This was followed by the organizing stage, which involved structuring task distribution and establishing a special team responsible for curriculum development. During the implementation stage, the principal adopted a transformational leadership model, providing training, technical guidance, and motivational support to teaching staff. Meanwhile, the controlling stage involved regular evaluations to ensure that the curriculum implementation process proceeded in accordance with the established plan. The final findings of this study indicate that the managerial strategies applied were considerably effective in enhancing teachers' acceptance of curriculum change. Nevertheless, a number of challenges remain and require ongoing, sustained intervention